Socio-economic investigation of osteoporosis patients - Shamas-ud Din; Naimatullah Hashmi (Masyarakat, Kebudayaan dan Politik, 2020)
Osteoporosis has become a public health problem risk factor worldwide and a deliberate disease that affects both women and men equally. The main objective of this study is to explore the socio-economic status of osteoporosis patients related to the occurrence of osteoporosis— the current study conducted at federal government hospitals in Islamabad. A quantitative research method used to collect data through a well-designed questionnaire. A stratified random sampling technique used to select a sample of 400 osteoporosis patients within 35-80 years. Mann-Whitney U Test applied for a dependent, independent variable, and frequency distribution tables used for univariate analysis. Results showed that osteoporosis patients were spending more money on their household expenditures than health. The socio-economic status of osteoporosis patients is essential for the prevention of osteoporosis and their treatment. Osteoporosis is one of the major global health issues associated with socio-economic status. The present study recommended that the improvement of socio-economic status and increasing the level of education could play a vital role in reducing the risks of osteoporosis.